SPORT AS AN ENGINE OF DEVELOPMENT. FROM HOPE TO FORGOTTEN.: THE TERRITORY OF THE VALLE DEL CHOTA - Perez Cabrera, Cesar Isaac (Revista Ecos de la Academia, 2022)
Sport has been an engine of socio-economic development at the beginning of the century in the Valle del Chota, during the process of the world cup in 2002, the Valle del Chota, became a very referential place for Ecuador for its sporting potential. The objective of the research is to show what impact sport has provided for local development in the Valle del Chota and how this process has been. The type of research was qualitative and the instruments used were the interview for a collection of data and opinions to citizens of the sector to be able to have information closer to the social and economic process of the area in the last 20As a result, it was evident that the spiral of exclusion has a great influence on the failed process of building a social capital that was to serve as a fundamental pillar for the cooperation of the actors within the Afro zone. The most relevant result of the research is the internal migration of the families of the different athletes due to lack of public policy support from government institutions for the socioeconomic promotion of the Valle del Chota